Critical Analysis of BAZNAS Financial Performance - Ahmad , Muhammad Malik Sayyid; Mulyati, Sri; Maulidha, Erina (Yayasan Mitra Peduli Indonesia, 2023)
This study aims to analyze and find out the financial performance of the National Amil Zakat Agency (BAZNAS) during the period 2014 to 2018. The measurement of financial performance is carried out using financial ratio indicators published by the BAZNAS Strategic Study Center (PUSKAS). The financial ratios consist of components of activity, efficiency, amil funds, liquidity, and growth. The objects used in this research are the financial statements, and / or annual reports of BAZNAS. The results of this study indicate that in terms of activity, it can be said that one ratio is less effective, one ratio is quite effective, five effective ratios, one ratio is very effective, then two ratios are not good conditions, five ratios are good conditions, and three ratios are very good conditions. In terms of efficiency, one ratio can be said to be quite efficient and one ratio is inefficient. In terms of amil funds, three ratios can be said to be in bad condition. In terms of liquidity, one ratio can be said to be in bad condition, and one ratio in good condition. In terms of growth, it can be said that one ratio is out of tune, two ratios are in good condition, and two ratios are in very good condition. BAZNAS still has to maintain good performance, and continue to make changes and improvements even better on a performance that has not been good